PERAN MUATAN LOKAL DALAM MENINGKATKAN PEMAHAMAN KEAGAMAAN SISWA - An Nahdliyah, Khumairoh (ILJ: Islamic Learning Journal, 2024)
The objective of this research is to describe the implementation of the local charge of early childhood education, improved understanding of religion, and the inhibitory factors that are present in implementing the local load of infant education in the SDN Pojokrejo Kesamben Jombang. In this study, the researchers used qualitative descriptive research methods. The methods used to collect data are: Observation, Interview, Documentation. Data in analysis by reducing the data that is not relevant, displays the data and draw research conclusions. As for the results of this study, the implementation of the local charge of maternal education in the SDN Pojokrejo Kesamben is going very well, all matters related to maternal Education are already structured. Interesting learning methods at the time of learning so that students do not get bored easily, there are school facilities in the form of a yellow book, there is a scraping of input of students' learning results for a year. The increased understanding of religion is seen from the average daily score and Semester Average Score (PTS) of Class VI. The inhibitory factors encountered in the implementation of early childhood education are that students are just beginning to know the letter, so they are not so skilled in writing it in conjunction and at home many of their parents can not read the writing so learning is only from their tutor. And the basic students on “training” is minimal, so the difficulty introducing students to the lessons books with basic writing.